2007
DOI: 10.1038/oby.2007.548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post‐absorptive and Postprandial Exercise on Glucoregulation in Metabolic Syndrome

Abstract: Objective: The aim of this study was to investigate the effects of an acute exercise bout in the morning in the post-absorptive or postprandial state on the glycemic and insulinemic response to three standardized meals throughout the day. It is hypothesized that post-absorptive exercise enhances fat oxidation rate during exercise and thereafter attenuates the glucose and insulin response to subsequent meals. Research Methods and Procedures: Seven sedentary males with metabolic syndrome (age, 45 Ϯ 11 years; BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 30 publications
7
44
1
Order By: Relevance
“…Studies of premeal (i.e., postabsorptive) exercise generally report either no effect on postchallenge glycemia (29,30) or an increase in the glycemic effect of a meal (26), which corroborates our findings regarding the effects of exercise performed at 4:30 p.m. on the subsequent dinner meal. Studies of postmeal exercise report improvements in postprandial glycemic control for as long as 4 h postchallenge, but not in response to the next meal (30), suggesting that these benefits are short-lived.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies of premeal (i.e., postabsorptive) exercise generally report either no effect on postchallenge glycemia (29,30) or an increase in the glycemic effect of a meal (26), which corroborates our findings regarding the effects of exercise performed at 4:30 p.m. on the subsequent dinner meal. Studies of postmeal exercise report improvements in postprandial glycemic control for as long as 4 h postchallenge, but not in response to the next meal (30), suggesting that these benefits are short-lived.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have investigated the role of exercise timing on glycemic responses to meals, primarily among younger or middle-aged people with type 2 diabetes and with the exercise timing ranging from premeal (26,27), immediately postmeal (25,28), 15–45 min postmeal (29,30), and 2 h postmeal (31). Studies of premeal (i.e., postabsorptive) exercise generally report either no effect on postchallenge glycemia (29,30) or an increase in the glycemic effect of a meal (26), which corroborates our findings regarding the effects of exercise performed at 4:30 p.m. on the subsequent dinner meal.…”
Section: Discussionmentioning
confidence: 99%
“…Most guidelines recommend postprandial moderate aerobic exercise for the prevention and treatment of glucose intolerance/diabetes mellitus 24) . It is reported that postabsorptive exercise has the advantage of promoting fat use, whereas postprandial exercise can attenuate the glycemic response to breakfast in sedentary males with metabolic syndrome 25) . Postprandial exercise may be more effective for lowering the glycemic impact of the evening meal in individuals with type 2 diabetes compared with pre-meal exercise 26) .…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that a single bout of exercise after a meal attenuates postprandial hyperglycemia in people with diabetes (Larsen, et al, 1997;Poirier, et al, 2001) and metabolic syndrome (Derave, et al, 2007). This observation is clinically important since postprandial hyperglycemia is a dominant and independent risk factor for cardiovascular disease in people with diabetes (Ceriello, 2004;Giugliano and Ceriello, 2001;Hanefeld, et al, 1996).…”
Section: Introductionmentioning
confidence: 99%